Graphene-based silicon negative electrode plate, preparation method and application thereof, and lithium ion battery

By adopting graphene-based silicon negative electrode sheets and using the combined structure of porous graphene and nano-silicon particles, the performance attenuation and safety problems caused by volume expansion of silicon material in lithium-ion batteries are solved, and a higher battery mass energy density and a simplified preparation process are achieved.

CN119864367APending Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311359543.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The volume expansion of silicon materials in traditional lithium-ion batteries during charging and discharging leads to battery performance attenuation and safety problems, and the prior art is difficult to effectively solve these problems.

Method used

A graphene-based silicon negative electrode sheet is used, which consists of a sheet structure formed by a porous graphene stack and nanosilicon particles embedded between the graphene sheet layers. The process is simplified by thermal reduction and roll pressing preparation methods and improve battery performance.

Benefits of technology

This technology effectively reduces the battery internal resistance and performance attenuation caused by volume expansion of silicon material, improves the structural stability and conductivity of the battery, improves the battery mass energy density, simplifies the preparation process, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864367A_ABST
    Figure CN119864367A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, and provides a graphene-based silicon negative electrode plate, a preparation method and application thereof, and a lithium ion battery. The graphene-based silicon negative electrode plate comprises a lamellar structure formed by stacking porous graphene and nano silicon particles located between graphene lamellar layers. The graphene-based silicon negative electrode plate provided by the invention has excellent structural stability and low resistance, can be directly used as a negative electrode plate of a lithium ion battery, solves the problem of volume expansion of a silicon material in an existing lithium ion battery, and can have better conductivity and higher battery mass energy density. The preparation method of the graphene-based silicon negative electrode plate is simple, low in cost and convenient for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and more specifically, to a graphene-based silicon negative electrode sheet and a preparation method and application thereof, as well as a lithium-ion battery. Background Art

[0002] The traditional lithium-ion battery pole piece preparation process is to mix and apply the active material, conductive agent and binder on the surface of the metal current collector to achieve the connection between the active material and the metal current collector. This preparation process is complicated, time-consuming and labor-intensive; and the long-term charge and discharge cycle of the battery will make the active material easily fall off the current collector, causing the battery internal resistance to increase and the performance to decay seriously.

[0003] Graphene is a two-dimensional sheet carbon material formed by the accumulation of single-layer carbon atoms. It has ultra-high ion mobility, good thermal conductivity, high light transmittance, excellent mechanical properties and good flexibility. At present, the graphene film obtained by using graphene oxide as a precursor and performing scraping, coating and sintering treatment can be used in heat dissipation and electric heating devices. The graphene film can be cut and tailored according to the actual shape requirements, and the graphene film can also be combined with other materials to meet more design functions and needs, which has great market potential.

[0004] Silicon materials can be used as negative electrode materials for lithium-ion batteries. They have the advantages of high specific capacity, good cycle performance and rate performance. However, the traditional preparation process seriously affects the application and promotion of silicon materials in batteries. Specifically, (1) the volume of silicon materials expands by about 300 times during the charge and discharge process, resulting in an increase in the thickness of the negative electrode plate and a deterioration in the stability of the plate; (2) the volume expansion of silicon materials leads to a decrease in the contact between silicon materials and the conductive agent and metal current collector, which affects the service life of lithium-ion batteries; (3) after the volume expansion of silicon materials, they are easy to fall off the current collector, which can easily cause safety problems such as self-discharge and internal short circuit.

[0005] In order to further improve the application of silicon materials in lithium-ion negative electrodes, researchers proposed to prepare porous silicon-based negative electrodes to solve the application problems of silicon materials from the structural aspect of the electrode. For example, the Chinese patent application with publication number CN101894940A adds a pore-forming agent to the silicon-based negative electrode slurry, and the high temperature causes the pore-forming agent to evaporate to form pores, thereby providing a buffer space for the silicon-based negative electrode. The Chinese patent application with publication number CN103633298A adds a plasticizer to the silicon-based negative electrode slurry, and solvent extraction dissolves the plasticizer to form pores, thereby providing a reserved space for the volume expansion of the silicon material. However, the above methods are all improved on the basis of the traditional copper-based coating process, and there is a problem of high process cost, and at the same time, the effect on improving the mass energy density of the battery is very small. In addition, the Chinese patent application with publication number CN115458718A discloses a method of adding an oxidant to a graphene oxide solution, and then hydrothermally preparing a three-dimensional gel of silicon and graphene, and compacting the three-dimensional gel to obtain an electrode sheet. However, this method has the problem of complex hydrothermal preparation and freeze-drying process of three-dimensional gel, making it difficult to achieve large-scale industrial production.

[0006] Therefore, it is of great significance to develop a negative electrode sheet with a simple preparation process that can effectively solve the volume expansion problem of silicon materials during the charging and discharging process. Summary of the invention

[0007] The purpose of the present invention is to provide a graphene-based silicon negative electrode plate and a preparation method thereof, so as to solve the technical problem of volume expansion of silicon materials during the charging and discharging process in the prior art.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] In a first aspect, the present invention proposes a graphene-based silicon negative electrode plate, comprising a sheet structure formed by stacking porous graphene sheets and nano-silicon particles located between the graphene sheets.

[0010] In the graphene-based silicon negative electrode plate provided by the present invention, a sheet structure formed by stacking porous graphene sheets is used as a conductive current collector, which has good conductivity, flexibility and mechanical processing performance, and can conduct and collect lithium-ion battery current to generate a maximum output current. Compared with using metal copper as a current collector, it can effectively improve the battery mass energy density; nano-silicon particles are embedded between graphene sheets, which can effectively reduce the contact resistance with the current collector, and solve the problems of increased volume of lithium-ion batteries caused by the volume expansion of silicon materials in the prior art, poor cycle performance, and internal short circuit and self-discharge.

[0011] According to some embodiments of the present invention, the pore size of the porous graphene is 2 to 50 nm.

[0012] According to some embodiments of the present invention, the median particle size of the nano-silicon particles is 50 to 200 nm.

[0013] According to some embodiments of the present invention, the nano silicon particles account for 40-80 wt % of the silicon negative electrode sheet.

[0014] According to some embodiments of the present invention, the thickness of the silicon negative electrode sheet is 50-100 μm.

[0015] According to some embodiments of the present invention, the conductivity of the silicon negative electrode plate is 3000 to 80000 S / m.

[0016] According to some embodiments of the present invention, the charge transfer impedance of the silicon negative electrode plate is 10 to 180Ω.

[0017] According to some embodiments of the present invention, the charge transfer impedance of the silicon negative electrode plate is 10-100Ω.

[0018] According to some embodiments of the present invention, the specific surface area of ​​the silicon negative electrode piece is 50 to 300 m 2 / g.

[0019] According to some embodiments of the present invention, the specific surface area of ​​the silicon negative electrode piece is 100 to 280 m 2 / g.

[0020] According to some embodiments of the present invention, the specific surface area of ​​the silicon negative electrode plate is 130 to 260 m 2 / g.

[0021] According to some embodiments of the present invention, the density of the silicon negative electrode plate is 1.6-2.0 g / cm 3 .

[0022] According to some embodiments of the present invention, the density of the silicon negative electrode plate is 1.65-1.9 g / cm 3 .

[0023] According to some embodiments of the present invention, the first coulombic efficiency of the silicon negative electrode plate is 75-90%.

[0024] According to some embodiments of the present invention, the capacity retention rate of the silicon negative electrode plate after 40 cycles is 55-75%.

[0025] According to some embodiments of the present invention, the capacity retention rate of the silicon negative electrode plate after 40 cycles is 60-72%.

[0026] In a second aspect, the present invention provides a method for preparing a graphene-based silicon negative electrode sheet, comprising:

[0027] S1. adding graphene oxide, a pore-forming agent and nano-silicon particles to a solvent and dispersing them to obtain a dispersion;

[0028] S2. forming the dispersion into a film and drying it to obtain a graphene oxide film;

[0029] S3. The graphene oxide film is subjected to thermal reduction treatment in an inert atmosphere, and then rolled to obtain the graphene-based silicon negative electrode plate.

[0030] The preparation method of the graphene-based silicon negative electrode plate provided by the present invention is to form a film after mixing graphene oxide, nano silicon and a pore-forming agent uniformly, sinter and form pores on the dried film in a protective atmosphere, and then obtain a porous graphene-based silicon negative electrode plate with supporting strength and excellent conductivity through roller compaction. The porous graphene-based silicon negative electrode plate can be directly applied to the negative electrode of the battery. The present invention realizes the reduction and pore formation of graphene through a one-step method, greatly simplifies the process of multi-step pore formation of the pole plate in the prior art, effectively reduces the pole plate preparation cost, and is convenient for large-scale production.

[0031] The graphene oxide used in the present invention can be a powder, a filter cake, a mud-like material prepared by a Hummers modification method, or a commercially available graphene oxide dispersion, a filter cake, a mud-like material, etc.

[0032] In the present invention, dispersion is preferably performed to achieve a uniform mixing effect of the components, which can be achieved by various conventional methods, such as any one or more combinations of stirring, sand milling, ball milling, and high-pressure homogenization.

[0033] According to some embodiments of the present invention, the dispersion is carried out by high-pressure homogenization, and the homogenization pressure is 30-100 MPa.

[0034] According to some embodiments of the present invention, the solvent comprises at least one of water, ethanol and methanol.

[0035] According to some embodiments of the present invention, the median particle size of the graphene oxide is 5 to 30 μm.

[0036] According to some embodiments of the present invention, the pore-forming agent includes at least one of piperazine, aminopiperazine, imidourea, urea, ammonium bicarbonate, ammonium carbonate, ammonium chloride, and ammonium sulfate.

[0037] The preparation method of the graphene-based silicon negative electrode plate provided by the present invention adopts a small molecule material that is easily volatile and decomposes to produce alkaline substances as a pore-forming agent, gently forms pores under relatively low temperature conditions, and better maintains the density between graphene sheets, so that the plate has the advantages of fewer defects and high conductivity.

[0038] According to some embodiments of the present invention, the pore-forming agent includes at least one of piperazine, aminopiperazine, and imidourea.

[0039] In the present invention, at least one of piperazine, aminopiperazine and imidourea is selected as a pore-forming agent. These organic small molecule pore-forming agents are combined with graphene through a small number of active sites, and can achieve etching of the graphene surface at a relatively low temperature. No side reactions occur during the pore-forming process, and no residue is left in the matrix after pore formation, thereby avoiding affecting the properties of the silicon material.

[0040] According to some embodiments of the present invention, the mass ratio of graphene oxide to pore-forming agent is 5 to 20:1.

[0041] According to some embodiments of the present invention, the mass ratio of the graphene oxide to the nano-silicon particles is 0.5-6:1.

[0042] According to some embodiments of the present invention, the concentration of graphene oxide in the dispersion is 0.5 to 7 wt %.

[0043] In the present invention, by controlling the concentration of graphene oxide in the dispersion, the dispersion can have a relatively suitable viscosity (eg, 100 to 100,000 cps), thereby ensuring a smooth film-forming process.

[0044] According to some embodiments of the present invention, the film forming includes coating a film on a substrate.

[0045] According to some embodiments of the present invention, the substrate includes any one of a PET film, a PI film, a PP film, an OPP film, a CPP film and a release film.

[0046] According to some embodiments of the present invention, the film has a thickness of 0.5 to 5 mm.

[0047] In the present invention, the drying method may adopt various common drying methods, such as blast drying, infrared drying, air duct drying, tunnel drying, etc.

[0048] According to some embodiments of the present invention, the drying temperature is 50-120°C.

[0049] According to some embodiments of the present invention, the thermal reduction treatment includes: first heating the temperature to 150-300°C at a heating rate of 0.1-1°C / min, and keeping it warm for 1-3 hours; then heating the temperature to 750-1100°C at a heating rate of 1-10°C / min, and keeping it warm for 2-5 hours.

[0050] According to some embodiments of the present invention, the inert atmosphere includes any one of nitrogen, helium and argon.

[0051] According to some embodiments of the present invention, the rolling pressure is 5-50 MPa.

[0052] In a third aspect, the present invention provides a graphene-based silicon negative electrode plate prepared by the preparation method described in the second aspect.

[0053] In a fourth aspect, the present invention provides the use of the graphene-based silicon negative electrode sheet described in the first aspect or the graphene-based silicon negative electrode sheet described in the third aspect in a battery, especially a lithium-ion battery.

[0054] In a fifth aspect, the present invention provides a lithium-ion battery, comprising the graphene-based silicon negative electrode sheet described in the first aspect or the graphene-based silicon negative electrode sheet described in the third aspect.

[0055] The beneficial effects of the present invention are at least:

[0056] The graphene-based silicon negative electrode plate provided by the present invention has excellent structural stability and low resistance, and can be directly used as the negative electrode plate of a lithium-ion battery, solving the problem of volume expansion of silicon materials in existing lithium-ion batteries, and can have better conductivity and higher battery mass energy density. The preparation method of the graphene-based silicon negative electrode plate is simple, low-cost, and easy to mass-produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is the SEM image of the negative electrode sheet of Example 1.

[0058] Figure 2 BET diagram of the negative electrode sheet of Example 1 and Comparative Example 1.

[0059] Figure 3 This is the pore size distribution diagram of the negative electrode sheet of Example 1 and Comparative Example 1.

[0060] Figure 4 It is a cycle stability test curve diagram of the negative electrode sheets of Example 1, Comparative Example 1 and Comparative Example 2.

[0061] Figure 5 It is an AC impedance test curve diagram of the negative electrode sheets of Example 1, Comparative Example 1 and Comparative Example 2.

[0062] Figure 6 for Figure 5 Equivalent circuit diagram of the electrode. DETAILED DESCRIPTION

[0063] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in combination with specific implementation methods. It should be understood that the specific implementation methods described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.

[0064] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0065] In the present invention, the electrochemical performance test is carried out using the Blue Electric LAND battery test system and the Chenhua CHI660E electrochemical workstation. The test conditions include: the test temperature is 25°C. The negative electrode material is directly used as the negative electrode, the metal lithium sheet is used as the positive electrode, a 1mol / L LiPF6 solution is used as the electrolyte, and a polypropylene microporous membrane is used as the diaphragm to assemble a CR2016 button battery. The cycle stability test is tested using the Blue Electric LAND battery test system. The charge and discharge rate of the first three cycles is 0.05C, and the voltage range is 0.005~1.5V. The cycle charge and discharge rate is 0.2C, and the voltage range is 0.005~1.5V. The EIS AC impedance was tested using Chenhua CHI660E electrochemical workstation. The amplitude of the AC voltage was 5mV, and the frequency test range was 100K~0.01Hz. The test results would derive the Nyquist curve, which is composed of a semicircle at high frequency and a slash at medium and low frequencies. The semicircle at high frequency represents the process of charge transfer between the electrode surface and the electrolyte. Its diameter indicates the electrochemical impedance caused by the charge transfer process in the electrochemical reaction, which is called the charge transfer impedance (Rct). The slash at the low frequency region represents the Warbug impedance (Rf) caused by the diffusion of lithium ions in the SEI film of the electrode material. Figure 6 The equivalent circuit diagram of the electrode is given.

[0066] In the present invention, a scanning electron microscope (SEM) is used to characterize the morphology of the electrode material. Specifically, the scanning electron microscope is a TECNALG2F20 (200 kv) model of FEI Company of the United States. The test conditions are: the sample is directly pressed on a sample stage containing a conductive tape, and then inserted into the electron microscope for observation. The observation uses a magnification of 8000 times.

[0067] In the present invention, the median particle size of the graphene sheet is obtained by dynamic light scattering characterization, using a laser particle size analyzer of the model MS-3000 of Malvern Panalytical. Test conditions: the sample is dispersed in deionized water with a concentration of 0.01 mg / ml, and the test is performed after 10 minutes of ultrasound, and the instrument shading setting range is 5-20%.

[0068] In the present invention, the specific surface area is tested using an ASAP2010 specific surface area and pore size distribution tester from Micromeritics, USA. Test conditions: temperature 77K, nitrogen environment.

[0069] In the present invention, the conductivity test is performed using a ST-2258C multifunctional digital four-probe tester produced by Suzhou Jingge Co., Ltd. The preparation steps are: cutting the prepared electrode into a 5×5 cm square, and then testing with a conductivity meter.

[0070] Example 1

[0071] (1) 10 g of graphene oxide filter cake (50% solid content, D50 of 25 μm) was dispersed in 90 g of deionized water to prepare a dispersion with a solid content of 5 wt%, 0.5 g of piperazine was added, stirred and dissolved completely, and then placed in a high-pressure homogenizer and homogenized twice at a pressure of 80 MPa to obtain a first dispersion.

[0072] (2) Weigh 1.5 g of nano-silicon powder (D50: 100 nm), add it to the first dispersion, stir and disperse it completely, and homogenize it twice in a high-pressure homogenizer at a pressure of 30 MPa to obtain a second dispersion.

[0073] (3) The second dispersion was coated on the CPP film by an automatic coating machine to form a film with a thickness of 2 mm, and the film was placed in a forced air drying oven. After complete drying at 80° C., the dry film was peeled off from the CPP film to obtain a silicon / graphene oxide film.

[0074] (4) The silicon / graphene oxide film obtained in step (3) is subjected to the following programmed temperature carbonization treatment: in a nitrogen atmosphere, the temperature is increased to 200°C at a rate of 0.2°C / min and kept at this temperature for 2 hours; then the temperature is increased to 800°C at a rate of 5°C / min and kept at this temperature for 3 hours; after cooling, the film is rolled at a pressure of 30 MPa to obtain the porous graphene-based silicon negative electrode plate having a thickness of 80 μm.

[0075] The conductivity of the electrode was tested using four probes and was 10000S / m.

[0076] Figure 1 This is a SEM picture of the negative electrode obtained in Example 1. From the picture, it can be seen that the graphene is arranged in layers, and nano-silicon is embedded between the graphene layers.

[0077] from Figure 2 It can be seen that the BET specific surface area of ​​the negative electrode obtained in Example 1 is 250 m 2 / g, and a type IV isotherm with a visible hysteresis cycle in the relative pressure P / P0 range of 0.4 to 1, indicating that the negative electrode sheet contains a large number of mesopores.

[0078] from Figure 3 The pore size distribution curve in further confirms that the negative electrode sheet obtained in Example 1 has a large number of 2-50 nm mesoporous structures.

[0079] The negative electrode sheet of Example 1 was used to make a battery, and the cycle stability test curve at 0.2C charge and discharge current was as follows: Figure 4 .from Figure 4 It can be seen that the first cycle discharge capacity of the negative electrode of Example 1 is 1965mAh / g, the first coulomb efficiency is 86%, and the capacity retention rate is 65% after 40 cycles. The battery is subjected to electrochemical AC impedance test, and the Nyqusit curve of the test is shown in Figure 5 ,from Figure 5 It can be seen that the curve consists of a semicircle at high frequency and oblique lines at medium and low frequencies. The equivalent radius of the semicircle at high frequency represents the charge transfer impedance Rct of the interface between the electrode and the electrolyte, which is 42Ω. This shows that the porous graphene and the stacked electrode layer play a dual role in increasing the conductivity of the electrode.

[0080] Comparative Example 1

[0081] The preparation method of the silicon negative electrode plate is the same as that of Example 1, except that 0.5 g of piperazine is not added. The obtained negative electrode plate has a thickness of 80 μm, and the conductivity of the plate is 15000 S / m when tested by four-probe.

[0082] from Figure 2 It can be seen that the BET specific surface area of ​​the negative electrode obtained in Comparative Example 1 is 22 m 2 / g; and the electrode obtained in Comparative Example 1 without pore-forming agent modification treatment does not show an obvious hysteresis cycle curve.

[0083] Figure 3 The pore size distribution curve in also further confirms that there is no mesoporous structure in the negative electrode sheet of Comparative Example 1 that has not been modified with a pore-forming agent.

[0084] The negative electrode sheet of Comparative Example 1 was used to make a battery, and the cycle stability test curve at 0.2C charge and discharge current was shown in Figure 4 .from Figure 4 It can be seen that the first cycle discharge capacity of the material in comparative example 1 is 1905mAh / g, the first coulomb efficiency is 75%, and the capacity retention rate is 60% after 40 cycles. The battery is subjected to electrochemical AC impedance test, and the Nyqusit curve of the test is shown in Figure 5 ,from Figure 5 It can be seen that the curve consists of a semicircle at high frequency and oblique lines at medium and low frequencies. The equivalent radius of the semicircle at high frequency represents the charge transfer impedance Rct of the interface between the electrode and the electrolyte, which is 251Ω. This shows that the graphene electrode without pore-forming agent modification forms a large impedance in the charge transfer path, affecting the performance of the material.

[0085] Comparative Example 2

[0086] Nano-silicon (D50 is 100 nm), commercial graphene powder (Changzhou Sixth Element Material Technology Co., Ltd., SE1231) and binder are slurried and coated on copper foil in a ratio of 8:1:1 to make a silicon negative electrode sheet.

[0087] The negative electrode sheet of Comparative Example 2 was used to make a battery, and the cycle stability test curve at 0.2C charge and discharge current was shown in Figure 4 .from Figure 4 It can be seen that the first cycle discharge capacity of the material in comparative example 2 is 1915 mAh / g, the first coulomb efficiency is 80%, and the capacity retention rate is 45% after 40 cycles. The battery is subjected to electrochemical AC impedance test, and the Nyqusit curve of the test is shown in Figure 5 ,from Figure 5 It can be seen that the curve consists of a semicircle at high frequency and oblique lines at medium and low frequencies. The equivalent radius of the semicircle at high frequency represents the charge transfer impedance Rct of the interface between the electrode and the electrolyte, which is 612Ω.

[0088] Comparative Example 3

[0089] The preparation method of the porous graphene-based silicon negative electrode plate is similar to that of Example 1, except that the temperature-programmed carbonization treatment conditions are different, specifically, the temperature is raised to 800°C at a rate of 5°C / min under a nitrogen atmosphere and kept at that temperature for 3 hours. The graphene film explosion phenomenon occurs and the electrode plate cannot be obtained.

[0090] Example 2

[0091] (1) 10 g of graphene oxide filter cake (40% solid content, D50 of 30 μm) was dispersed in 790 g of deionized water to prepare a dispersion with a solid content of 0.5 wt%, 0.2 g of piperazine was added, stirred and dissolved completely, and then placed in a high-pressure homogenizer and homogenized twice at a pressure of 60 MPa to obtain a first dispersion.

[0092] (2) Weigh 4 g of nano-silicon powder (D50: 180 nm), add it to the first dispersion, stir and disperse it completely, and homogenize it twice in a high-pressure homogenizer at a pressure of 40 MPa to obtain a second dispersion.

[0093] (3) The second dispersion was coated on a PP film by an automatic coating machine to form a film with a thickness of 5 mm, and the film was placed in a forced air drying oven. After being completely dried at 100° C., the dry film was peeled off from the PP film to obtain a graphene oxide / silicon negative electrode film.

[0094] (4) The silicon / graphene oxide film obtained in step (3) is subjected to the following programmed temperature carbonization treatment: in a nitrogen atmosphere, the temperature is increased to 300°C at a rate of 0.1°C / min and kept at this temperature for 1 hour; then the temperature is increased to 1000°C at a rate of 10°C / min and kept at this temperature for 2 hours; after cooling, the film is rolled at a pressure of 30 MPa to obtain the porous graphene-based silicon negative electrode plate having a thickness of 95 μm.

[0095] Example 3

[0096] (1) 10 g of graphene oxide filter cake (60% solid content, D50 of 5 μm) was dispersed in 70 g of deionized water to prepare a dispersion with a solid content of 7.5 wt%, 1 g of piperazine was added, stirred and dissolved completely, and then homogenized twice in a high-pressure homogenizer at a pressure of 100 MPa to obtain a first dispersion.

[0097] (2) Weigh 4 g of nano-silicon powder (D50: 50 nm), add it to the first dispersion, stir and disperse it completely, and homogenize it twice in a high-pressure homogenizer at a pressure of 40 MPa to obtain a second dispersion.

[0098] (3) using an automatic coating machine to coat the second dispersion on a PET film into a film with a thickness of 1 mm, placing the film in a blast drying oven, and peeling the dry film off the PET film after drying at 50° C. to obtain a graphene oxide / silicon negative electrode film.

[0099] (4) The silicon / graphene oxide film obtained in step (3) is subjected to the following programmed temperature carbonization treatment: in a nitrogen atmosphere, the temperature is increased to 150°C at a rate of 1°C / min and kept at this temperature for 3 hours; then the temperature is increased to 750°C at a rate of 1°C / min and kept at this temperature for 5 hours; after cooling, the film is rolled at a pressure of 40 MPa to obtain the porous graphene-based silicon negative electrode plate having a thickness of 50 μm.

[0100] Comparative Example 4

[0101] The preparation method of the porous graphene-based silicon negative electrode plate is similar to that of Example 3, except that the temperature-programmed carbonization treatment conditions are different, specifically, the temperature is raised to 750°C at a rate of 1°C / min under a nitrogen atmosphere and kept at that temperature for 5 hours. The graphene film explosion phenomenon occurs and the electrode plate cannot be obtained.

[0102] Example 4

[0103] The method for preparing the porous graphene-based silicon negative electrode plate is similar to that of Example 1, except that piperazine is replaced by an equal mass of aminopiperazine.

[0104] Example 5

[0105] The preparation method of the porous graphene-based silicon negative electrode plate is similar to that of Example 1, except that piperazine is replaced by an equal mass of imidourea.

[0106] Example 6

[0107] The method for preparing the porous graphene-based silicon negative electrode plate is similar to that of Example 1, except that piperazine is replaced by an equal mass of ammonium chloride.

[0108] Example 7

[0109] The method for preparing the porous graphene-based silicon negative electrode plate is similar to that of Example 1, except that piperazine is replaced with an equal mass of ammonium bicarbonate.

[0110] Example 8

[0111] The method for preparing the porous graphene-based silicon negative electrode plate is similar to that of Example 1, except that piperazine is replaced with an equal mass of urea.

[0112] Silicon anode electrode performance evaluation

[0113] The performance indicators of the silicon negative electrode sheets of the embodiments and comparative examples were tested, and the results are shown in the following table.

[0114]

[0115] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A graphene-based silicon negative electrode plate, characterized in that: It includes a sheet structure formed by stacking porous graphene and nano silicon particles located between the graphene sheets.

2. The graphene-based silicon negative electrode sheet according to claim 1, characterized in that: The pore size of the porous graphene is 2 to 50 nm; And / or, the median particle size of the nano silicon particles is 50 to 200 nm; And / or, the nano silicon particles account for 40-80wt% of the silicon negative electrode plate; And / or, the thickness of the silicon negative electrode plate is 50-100 μm; And / or, the conductivity of the silicon negative electrode plate is 3000-80000 S / m; And / or, the charge transfer impedance of the silicon negative electrode plate is 10 to 180Ω; And / or, the specific surface area of ​​the silicon negative electrode plate is 50 to 300 m 2 / g; And / or, the density of the silicon negative electrode plate is 1.6-2.0 g / cm 3 ; And / or, the first coulombic efficiency of the silicon negative electrode plate is 75-90%; And / or, the capacity retention rate of the silicon negative electrode plate after 40 cycles is 55-75%.

3. A method for preparing a graphene-based silicon negative electrode sheet, characterized in that: include: S1. adding graphene oxide, a pore-forming agent and nano-silicon particles to a solvent and dispersing them to obtain a dispersion; S2. forming the dispersion into a film and drying it to obtain a graphene oxide film; S3. The graphene oxide film is subjected to thermal reduction treatment in an inert atmosphere, and then rolled to obtain the graphene-based silicon negative electrode sheet.

4. The preparation method according to claim 3, characterized in that: The median particle size of the graphene oxide is 5 to 30 μm; And / or, the pore-forming agent includes at least one of piperazine, aminopiperazine, imidourea, urea, ammonium bicarbonate, ammonium carbonate, ammonium chloride, and ammonium sulfate; preferably, the pore-forming agent includes at least one of piperazine, aminopiperazine, and imidourea.

5. The preparation method according to claim 3 or 4, characterized in that: The mass ratio of graphene oxide to pore-forming agent is 5 to 20:1; And / or, the mass ratio of the graphene oxide to the nano-silicon particles is 0.5 to 6:1; And / or, the concentration of graphene oxide in the dispersion is 0.5-7wt%.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The film forming includes coating on a substrate; preferably, the substrate includes any one of a PET film, a PI film, a PP film, an OPP film, a CPP film and a release film; And / or, the film thickness of the film is 0.5 to 5 mm; And / or, the drying temperature is 50-120°C.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The thermal reduction treatment comprises: firstly heating the temperature to 150-300°C at a heating rate of 0.1-1°C / min, and keeping the temperature for 1-3 hours; then heating the temperature to 750-1100°C at a heating rate of 1-10°C / min, and keeping the temperature for 2-5 hours; And / or, the inert atmosphere includes any one of nitrogen, helium and argon.

8. A graphene-based silicon negative electrode sheet prepared by any one of claims 3-7.

9. Use of the graphene-based silicon negative electrode sheet according to claim 1 or 2 or the graphene-based silicon negative electrode sheet according to claim 8 in batteries, especially lithium-ion batteries.

10. A lithium ion battery, characterized in that: It includes the graphene-based silicon negative electrode sheet as described in claim 1 or 2 or the graphene-based silicon negative electrode sheet as described in claim 8.

Citation Information

Patent Citations

  • Porous silicon-based cathode for lithium battery and preparation method thereof

    CN101894940A

  • Lithium ion battery silicon negative electrode sheet and preparation method thereof, and lithium ion battery

    CN103633298A

  • Preparation method of silicon and porous graphene layered electrode material with high-quality silicon-carbon contact interface

    CN115458718A